Antiangiogenesis in recurrent glioblastoma: proof of principle - Nossek, Erez (PAGEPress Publications, 2009)
Glioblastoma multiforme, a neoplasm with variable histological and biological features, is characterized by diverse imaging features, including highly heterogeneous enhancement. This reflects variable disruption of the blood brain barrier and inherent differences in the vascularity of the tumor. Experience in treating malignant glioma with antiangiogenic drugs is growing, and the most commonly used, in combination with irinotecan or other cytotoxic agents as salvage therapy, is bevacizumab, a monoclonal antibody against vascular endothelial growth factor. A 42-year-old, right-handed person with recurrent glioblastoma multiforme presented with two synchronous foci of recurrent disease in follow-up: one area with enhancement and another one nonenhancing and infiltrative, which responded differently to treatment with bevacizumab and irinotecan. Our example demonstrates the heterogeneous nature of glioblastoma multiforme and is proof of principle for antiangiogenic treatment in selected enhancing, presumably angiogenic forms of glioblastoma multiforme. Antiangiogenic treatment may be ineffective in more infiltrative, biologically different lesions.